PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA UD. SUN FLOWER - Dewi Cantika Rahmawati; Sri Lestari (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
Previous studies show that the matter about compensation, workplace stress, and the work environment improves work productivity has a significant impact. The purpose of this article is to create hypotheses about the influence between variables for use in future research. This is a literature study on HR management. The results of this research are supported theoretically and phenomenologically, and it can be concluded that work productivity (Y) is influenced by compensation (X1), work environment (X2), and work stress (X3). Hence, the findings suggest that such factors need to be considered in the context of management strategies to improve workforce effectiveness and efficiency across different types of organizations.